أهمية معايرة البروتين الارتكاسي C للمصل والسائل الدماغي الشوكي في تدبير التهاب السحايا عند الأطفال - إبراهيم, علي; مروشية, فيصل; الدو, إياد (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 42 مريضا قبلوا في قسم الأطفال في مشفى الأسد الجامعي خلال عام (2003- 2004) بتشخيص التهاب سحايا من خلال البزل القطني والذي اعتبر إيجابيا وفق القيم التالية: 1- الولدان: > 20 خلية لمفاوية أو > 10 خلايا كثيرات النوى. 2- الرضع والأطفال: > 5 خلايا لمفاويات أو كثيرات نوى. لقد تم معايرة القيم المخبرية التالية عند جميع المرضى: - الدم: تعداد كامل، سكر الدم، البروتين الارتكاسي C (CRP). - السائل الدماغي الشوكي: تعداد الكريات البيض، سكر ، بروتين ، CRP ، والزرع. لقد قمنا بتقسيم المرضى إلى المجموعات التالية: 1- الولدان: شملت المجموعة 12 مريضا (8 ذكور، 4 إناث)، كان CRP السائل الدماغي الشوكي إيجابيا في 7 مرضى فقط وكانت الحساسية 58 %، ولا يوجد أي علاقة بين تعداد الكريات البيض في السائل الدماغي الشوكي وقيمة CRP فيه، ولقد كان CRP المصل إيجابيا في جميع المرضى وبحساسية 100 %. 2- الأطفال دون عمر السنتين: شملت المجموعة 20 مريضا (12 ذكر، 8 إناث)، شخص لهم التهاب سحايا جرثومي في 8 حالات (40%) والتهاب سحايا فيروسي في 12 حالة، كانت حساسية CRP في السائل الدماغي الشوكي والمصل 100 % ونوعية CRP السائل الدماغي الشوكي والمصل 75 % ،25 % على التوالي ، وقيمة تنبؤ إيجابية 73 % ، 50 % على التوالي ، وقيمة تنبؤ سلبية 100 % ، 75 % على التوالي . 3- الأطفال بعد عمر السنتين: شملت المجموعة 10 مرضى (7 ذكر، 3 أنثى) شخص لهم التهاب سحايا جرثومي في 5 حالات (50%) وكانت حساسية CRP السائل الدماغي الشوكي و المصل 100%، 80% على التوالي، والنوعية كانت 100%، 50 % على التوالي، وقيمة التنبؤ الإيجابية 100 % ، 50 % على التوالي وقيمة التنبؤ السلبية 100% و50% على التوالي. The study included 42 patients admitted to Pediatrics Department in AL-ASSAD University Hospital in the year (2003-2004), with diagnosis of meningitis by lumbar puncture which was considered positive according to the following values: 1- Newborns: > 20 lymphocyte or > 10 polymorphinuclear cells. 2- Infants and children: > 5 lymphocytes or polymorphinuclear cells. The following laboratory parameters were performed to all patients: - Blood: complete blood count, sugar, CRP. - Cerebrospinal fluid (C.S.F): white blood cell count, sugar, protein, CRP, and culture. We divided the pateints into the following groups: 1- Newborn group: this group included 12 patients (8♂, 4 ♀), and C.S.F CRP was positive in only 7 patients, with sensitivity of 58 % and there was no relationship between WBC in C.S.F and the value of CRP in C.S.F, serum CRP was positive in all patients with sensitivity of 100 % . 2- Children aged less than 2 years: it included 20 patients (12 ♂,8 ♀), bacterial meningitis was diagnosed in 8 patients (40%) and viral meningitis in 12 patients, sensitivity of C.S.F CRP and serum CRP was 100 %, specifity of C.S.F CRP and serum CRP was 75 %, 25 % respectively, and positive predictive value was 73 %, 50 % respectively, negative predictive value was 100%, 75 % respectively. 3- Children aged more than 2 years: included 10 patients (7 ♂, 3 ♀), bacterial meningitis was diagnosed in 5 patients( 50 %), sensitivity of C.S.F CRP and serum CRP was 100%, 80 % respectively, and specifity was 100%, 20 % respectively, positive predictive value was 100%, 50 % respectively, negative predictive value was 100%, 50 % respectively .